Strategy for Accepting New Students Post-COVID-19: A Case Study - Munawarah, Munawarah; Ikhsan, Ikhsan; Fajzrina, Lati Nurliana Wati; Aulia, Reza; Fadillah, Chairun Nisa (Al-Athfal: Jurnal Pendidikan Anak, 2022)
Purpose – The impact of COVID-19 has created new problems in the world of education. In addition to the decreasing number of students, the community prefers to provide education to children at home. It makes the education reflection worse because of the minimum number of students. For this reason, in the new normal or post-COVID-19 era, a strategy is needed to increase the number of students. In addition, the purpose of this study was to find out the strategies used in accepting new students after COVID-19. Then, find out the management of new student admissions at PAUD IT ADAR.Design/methods/approach – The method used was a qualitative methods, the research describes a descriptive narrative and is strengthened by data in the field obtained through interviews, filling out questionnaires, and direct observation.Findings – The results of this study showed that the new student acceptance strategy was carried out by distributing brochures, repairing facilities and infrastructure or modernizing facilities and infrastructure, enriching relationships, teaching creativity, and providing good service. The management function is carried out by planning related to the new student admissions program, then organizing to form several work groups and teams, for implementing initiatives referring to the initial planning following the strategy carried out, then for evaluating the activities of institutional personnel who conduct evaluation meetings.Research implications/limitations – The limitation of this study is the lack of quantitative data (numbers), which improves the theoretical findings. The strategy for accepting new students indeed post-COVID 19 in PAUD IT ADAR. Practical implications – The research suggests that adequately utilizing of the management function can effectively run the post-COVID-19 student acceptance strategy in early childhood institutions. It requires cooperation from various parties and a mature process, including planning, implementation, and evaluation. Good planning and cooperation are necessary to achieve the goal, and the implemented strategy can serve as a best practice for other early childhood education institutions.Originality/value – The management of implementing the new student admissions program post-COVID-19 can help teachers increase the number of students. Paper type Case study